Content Analysis and Student Perceptions of “Ayo Fasih Berbahasa Arab” Book - Misdayanti, Annisah; Roojil Fadillah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to analyze the suitability of the textbook